The role of hospital antimicrobial and infectious diseases pharmacists in the UK: a theoretically underpinned exploration. Issue 1 (11th January 2023) - Micallef, C; Enoch, D A; Kamranpour, P; Santos, R; Tyler, N; Scott, S
Abstract: Objectives: We sought to characterise the role of hospital infection pharmacists in the UK and to understand the core challenges being faced, future role development desires and the required support to address these. Methods: We developed a questionnaire underpinned by the theoretical domains framework exploring the barriers and enablers to pharmacists fulfilling their perceived roles and responsibilities. Any pharmacist whose role included 'specialist antimicrobial' or 'infectious diseases' was invited to complete a questionnaire sent via national infection and pharmacy groups/networks. Descriptive statistics were used to report responses to each item, and a content analysis was undertaken to summarize the key messages from an extended response option. Results: Of the 102 respondents, 91 (89.2%) were from English hospitals. Fifty-three (52%) were from district general hospitals and 45 (45.1%) from teaching hospitals. Most (97, 95%) respondents were of a senior grade. The need for a comprehensive educational programme, recognition of research as core to the role and integration with infection/microbiology departments were key requirements along with protected time to engage with the activities. Highlights of the role were opportunities to teach, making a significant contribution to patient care and scope to contribute to strategy and vision. The COVID-19 pandemic negatively impacted on respondents' capacity to undertake their perceived roles and responsibilities. Conclusions: Our study delineates the need for UK infection and pharmacy policy makers to review hospital infection pharmacist developmental pathways and roles. Joint learning, and closer working, with infection/microbiology departments may be an efficient strategy to address the issues raised.